Comparison Between Pressure Swing Adsorption and Liquid Oxygen Enrichment Techniques in the Atacama Large Millimeter/Submillimeter Array Facility at the Chajnantor Plateau (5,050 m) - Lopez, Ivan; Aravena, Reinaldo; Soza, Daniel; Morales, Alicia; Riquelme, Silvia; Calderon-Jofré, Rodrigo; Moraga, Fernando A. (Frontiers in Physiology, 2021)
The Chilean workforce has over 200,000 people that are intermittently exposed to altitudes over 4000 m. In 2012, the Ministry of Health provided a technical guide for high altitude workers that included a series of actions to mitigate the effects of hypoxia. Previous studies have shown the positive effect of oxygen enrichment at high altitudes. The Atacama Large Millimeter / submillimeter Array (ALMA) radiotelescope operates at 5,050 m (Array Operation Site, AOS) and is the only place in the world where Pressure Swing Adsorption (PSA) and Liquid Oxygen technologies have been installed at a large scale. These technologies reduce the equivalent altitude by increasing oxygen availability. This study aims to perform a retrospective comparison between the use of both technologies during operation in ALMA at 5,050 m. In each condition, variables such as O2, temperature, and humidity were continuously recorded in each AOS rooms, and cardiorespiratory variables were registered. In addition, we compared portable oxygen by using continuous or demand flow during outdoors activities at very high altitudes. The outcomes showed no differences between production procedures (PSA or Liquid oxygen) in regulating oxygen availability at AOS facilities. As a result, big-scale installations have difficulties reaching the appropriate oxygen concentration due to leaks in high mobility areas. In addition, the PSA plant requires adequacy and maintenance to operate at a very high altitude. A continuous flow of 2-3L/min of portable oxygen is recommended at 5,050m.